2021
DOI: 10.1186/s13058-021-01410-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast cancer development by tumor characteristics among women with benign breast disease

Abstract: Background Among women diagnosed with invasive breast cancer, 30% have a prior diagnosis of benign breast disease (BBD). Thus, it is important to identify factors among BBD patients that elevate invasive cancer risk. In the general population, risk factors differ in their associations by clinical pathologic features; however, whether women with BBD show etiologic heterogeneity in the types of breast cancers they develop remains unknown. Methods Usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
(87 reference statements)
2
15
0
5
Order By: Relevance
“…Several studies have suggested that rs1136200 polymorphisms in the HER2 gene may be genetic risk factors for breast broadenoma in South Indians. However, some evidence indicates that the polymorphism rs1058808 is not a signi cant risk factor [29]. Finally, this research has certain limitations.…”
Section: Demographic and Clinical Characteristics Of Fa And Controlsmentioning
confidence: 79%
“…Several studies have suggested that rs1136200 polymorphisms in the HER2 gene may be genetic risk factors for breast broadenoma in South Indians. However, some evidence indicates that the polymorphism rs1058808 is not a signi cant risk factor [29]. Finally, this research has certain limitations.…”
Section: Demographic and Clinical Characteristics Of Fa And Controlsmentioning
confidence: 79%
“…These programs might not contain the answer to their questions, because to our knowledge, no study has investigated this issue up to now. On the other side, in patients affected by known high-risk benign breast diseases, the approach and management offered by the health-care provider gives some significant information to the patients [14,26]. A literature search, however, shows no specific study aiming at the knowledge gaps in this group.…”
Section: Discussionmentioning
confidence: 99%
“…This is only made possible when the patient seeks medical help in the early stages, which means before the appearance of any symptom, or as early as the first manifestations [10]. On the other hand, some lesions of the breast precede the manifestation of breast cancer, and timely diagnosis of these precancerous lesions can assist in breast cancer prevention [11][12][13][14]. For this early detection to happen, it is necessary for women to be examined in appropriate times but this will only be possible if women are aware of this necessity.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has long shown that mRNAs, miRNAs, lncRNAs, and circRNAs can be used as diagnostic and prognostic biomarkers for certain cancers [23,24,25,26,27,28]. Genetic signature-based risk models have also been widely reported to show high prognostic accuracy in many other cancer types [29,30,31,32]. For example, in Sun's research, ROC curves showed that the AUC of hsa circ 0035445 was 0.68 and 0.86 in tissues and plasma respectively, suggesting hsa circ 0035445 had the potential in distinguishing tumor tissues from normal tissues [33].…”
Section: Discussionmentioning
confidence: 99%